Comparative morphology and plant volatile responses of antennal sensilla in Cinara cedri (Hemiptera: Lachninae), Eriosoma lanigerum (Hemiptera: Eriosomatinae), and Therioaphis trifolii (Hemiptera: Calaphidinae) - Yang, Lu-Lu; Wang, Bing; Shen, Jie; Wang, Gui-Rong (Frontiers in Cellular Neuroscience, 2023)
Olfaction is important for mediating aphid behaviors and is involved in host location and mating. Antennal primary rhinaria play a key role in the chemoreception of aphids. The function of the peripheral olfactory system in the subfamily Aphidinae has been intensively studied, but little is known about other subfamilies of Aphididae. Therefore, three aphid species were selected to study the olfactory reception of plant volatiles: Cinara cedri (Lachninae), Eriosoma lanigerum (Eriosomatinae), and Therioaphis trifolii (Calaphidinae). In this study, the morphology and distribution of the antennal sensilla of apterous adults were observed by scanning electron microscopy. Three morphological types were identified (placoid sensilla, coeloconic sensilla, and trichoid sensilla); the first two were distributed on the antennal primary rhinaria. A pattern of primary rhinaria in C. cedri was found that differed from that of E. lanigerum and T. trifolii and consists of 1 large placoid sensillum (LP) on the 4th segment, 2 LPs on the 5th segment, and a group of sensilla on the 6th antennal segments. Later, we recorded and compared neuronal responses of the distinct placoid sensilla in the primary rhinaria of the three aphid species to 18 plant volatiles using a single sensillum recording (SSR) technique. The results indicated that the functional profiles based on the tested odorants of the primary rhinaria of the three investigated aphid species were clustered into three classes, and exhibited excitatory responses to certain types of odorants, especially terpenes. In C. cedri, the ORNs in LP6 exhibited the highest responses to (±)-citronellal across all tested chemicals, and showed greater sensitivity to (±)-citronellal than to (+)-limonene. ORNs in LP5 were partially responsive to α-pinene and (-)-β-pinene in a dose-dependent manner. E. lanigerum showed significantly stronger neuronal responses of LP5 to several terpenes, such as (-)-linalool and α-terpineol, compared to other species. In T. trifolii, the neuronal activities in LP6 showed a greater response to methyl salicylate as compared to LP5. Overall, our results preliminarily illustrate the functional divergence of ORNs in the primary rhinaria of aphids from three subfamilies of Aphididae and provide a basis for better understanding the mechanism of olfactory recognition in aphids.